Epidemiology of breast cancer in Malaysia - Yip, C.H.; Taib, N.A.; Mohamed, I. (West Asia Organization for Cancer Prevention, 2006)
Data from the National Cancer Registry of Malaysia for 2004 provide an age-standardised incidence rate (ASR) of 46.2 per 100,000 women. This means that approximately 1 in 20 women in the country develop breast cancer in their lifetime. However, the rate differs between the three main races, the Malays, Chinese and Indians. The age standardized incidence in Chinese is the highest, with 59.7 per 100,000, followed by the Indians at 55.8 per 100,000. The Malays have the lowest incidence of 33.9 per 100,000. This translates into 1 in 16 Chinese, 1 in 16 Indian and 1 in 28 Malay women developing breast cancer at some stage in their lives. The commonest age at presentation is between 40-49 years, with just over 50% of the cases under the age of 50 years, 16.8% below 40, and 2% under 30. Some 55.7% of all cases were found to be ER positive. The commonest presenting symptom was a lump in the breast in over 90% of cases, generally felt by the woman herself. The mean size of the lump was 4.2 cm, and on average, the women waited 3 months before seeking medical attention. Over the 12-year period from 1993 to 2004, about 60-70% of women presented with early stage (Stages 1-2) while 30-40% presented with late breast cancer (Stages 3-4). Especially Malays present at later stages and with larger tumours. Consequently their survival is worse than with Chinese and Indian women. The challenge in Malaysia is to be able to provide a comprehensive service in the diagnosis and treatment of breast cancer, and this requires training of a team of health professionals dedicated to breast health, such as breast surgeons, radiologists specializing in breast imaging, breast pathologists, plastic surgeons specializing in breast reconstruction, medical and radiation oncologists, psycho-oncologists, counselors, and breast nurses. Advocacy can play a role here in galvanizing the political will to meet this challenge.